Autonomous agents and multiagent systems : AAMAS 2016 Workshops, Best papers, Singapore, Singapore, May 9-10, 2016, Revised selected papers /: AAMAS 2016 Workshops, Best papers, Singapore, Singapore, May 9-10, 2016, Revised selected papers. (2016) - Unknown
No abstract available